From Electoral Epidemic to Government Epidemic: The Next Level of the Crisis in Southern Europe. Issue 4 (1st October 2016) - Bosco, Anna; Verney, Susannah
Abstract: With the elections of 2015–16 in Greece, Spain and Portugal, the political fallout from the economic crisis in Southern Europe reached a new level. An overview of the new electoral arenas and party systems is followed by an investigation of the paths to government formation. Unprecedented events during (multiple) processes of government formation, uncharted outcomes in government types and governing party identities, and the necessity to repeat elections are three features defining a new syndrome that first appeared in Greece but has now spread to Iberia. In Southern Europe the road to incumbency has become arduous and the risk of government instability high .